Electrochemical characteristics and transport properties of Fe(II)/Fe(III) redox couple in a non-aqueous reline deep eutectic solvent. (1st February 2015) - Xu, Q.; Zhao, T.S.; Wei, L.; Zhang, C.; Zhou, X.L.
Highlights: The Fe 2+ /Fe 3+ redox reaction in reline DES is shown to be quasi-reversible. The charge transfer coefficient of this redox reaction in reline is 0.44. The transport properties in reline are similar to those in conventional ILs. High solubility in reline is attributed to the formation of hydrogen bond donors. Abstract: Deep eutectic solvent (DES) is a promising electrolyte for non-aqueous redox flow batteries as it offers unique advantages including a wide electrochemical window, low vapor pressure and ease in preparation. In this work, the electrochemical characteristics of the Fe(II)/Fe(III) redox couple and the transport properties of ferric ions in the reline DES are studied. The cyclic voltammetry (CV) curves show that the redox reaction is quasi-reversible with the charge transfer coefficient of 0.44 at room temperature. The diffusivity, viscosity, conductivity of ferric ions in the reline DES are measured at different temperatures. The results indicate that the transport properties are similar to those for conventional ionic liquids. The high solubility of ferric ions in the reline DES is attributed to the formation of hydrogen bond donors, which is confirmed by the FT-IR absorption spectra analysis.